Development of Privacy Features on Anecdata.org, a Free Citizen Science Platform for Collecting Datasets for Climate Change and Related Projects - Bailey, Cait; Farrell, Anna; Purty, Turam; Taylor, Ashley; Disney, Jane (Frontiers in Climate, 2021)
The Anecdata website and its corresponding mobile app provide unique features to meet the needs of a wide variety of diverse citizen science projects from across the world. The platform has been developed with the help of continuous feedback from community partners, project leaders, and website users and currently hosts more than 200 projects. Over 8000 registered users have contributed more than 30,000 images and over 50,000 observations since the platform became open to the public in 2014. From its inception, one of the core tenets of Anecdata’s mission has been to make data from citizen science projects freely accessible to project participants and the general public, and in the platform’s first few years, it followed a completely open data access model. As the platform has grown, hosting ever more projects, we have found this model does not meet all project needs, especially where endangered species, property access rights, participant safety in the field, and personal privacy are concerned. We first introduced features for data and user privacy as part of “All About Arsenic”, an NIH/NIGMS Science Education Partnership Award (SEPA)-funded project at MDI Biological Laboratory which engages middle- and high-school teachers and students from schools across Maine and New Hampshire in sampling their home well water for analysis of arsenic and other heavy metals. In order to host this project on Anecdata, we developed features for spatial privacy or “geoprivacy” to conceal the coordinates of samplers’ homes; partial data redaction tools we call “private fields” to withhold certain sample registration questions from public datasets; and “participant anonymity”, to conceal which user account uploaded an observation. We describe the impetus for the creation of these features, the challenges we encountered, and our technical approach. While these features were originally developed for the purposes of a public health and science literacy project, they are now available to all project leaders setting up projects on Anecdata.org and have been adopted by a number of projects, including Mass Audubon’s Eastern Meadowlark Survey, South Carolina Aquarium’s SeaRise, and Coastal Signs of the Season (SOS) Monitoring projects.